Extraction and Summarization of Reviews using Lexicon based Approach. Issue 1 (January 2021) - Sheikh, A A; Arif, T; Malik, M B; Bhat, S I
Abstract: Online service providers have enabled users to freely comment in the form of review on an online items. These large scale of reviews contains valuable information and poses the need of automatic summarization. In this paper the extraction and summarization of reviews expressed by customers on Samsung mobiles has been carried out. The proposed approach extracts the Samsung reviews using custom build scraper from Flipkart and classify them as positive, negative and neutral using Lexicon based approach (SentiWordNet).